(untitled) (REVISTA DE AGRICULTURA NEOTROPICAL, 2021)
Beans are one of the most important crops in Brazil but still have a low yield. The use of technologies such as the application of biostimulants can provide greater yield for the crop. Thus, the work aimed to evaluate the effect of using Azospirillum brasilense and phytohormones on Jalo Precoce beans. The experiment was carried out in randomized blocks with nine treatments and four replications. The treatments consisted of a control, Stimulate (compound of phytohormones), and A. brasilense applied isolated or associated to the seeds or in a furrow. The plant height, stem diameter, shoot dry matter, number of pods per plant, number of grains per pod, the weight of grains per pod, and 100-grain weight were favored by A. brasilense and compound of phytohormones. The highest yield of Jalo Precoce beans (2218 kg ha-1) was obtained using the A. brasilense + phytohormone compound applied in the sowing furrow. The grain yield of Jalo Precoce beans showed a high positive correlation with the number of pods per plant and medium correlation with stem diameter and shoot dry matter.